Causes et métaphore - Pauna, Ramona (Neophilologica, 2008)
The metaphor has been principally considered within the frame of the first-order predicates, which means within the frame of a simple sentence. The metaphor is manifested as well in causal expressions which put the second order predicates into play. In the first case, the author of the article studies the nominal predicates origin, source, germ and in the second verbs to light and to kindle. The author makes an attempt to prove that the linguistic causality corresponds to semantic relations much more complex than this given by the traditional definition of this notion.